Comparative Benefit of Evening Primrose Oil and Soybean Oil on Treatment Satisfaction and Quality of Life among Postmenopausal Women - raghad mohammed; Manal Khalid Abdulridha; Bushrah Abd Al-Jbori (College of Pharmacy / Mustansiriyah University, 2024)
Background: Medicinal herbs as alternative therapies, commonly used to treat menopausal symptoms, and some studies have shown that they can be useful in treating menopausal syndrome, which have been linked to worse self-rated health, and decreased work productivity. Aim of the study: This study compared the effectiveness of EPO and Soybean Oil herbal supplement in a sample of Iraqi postmenopausal women on treatment satisfaction and their quality of life. Patients and methods: This prospective study conducted on 20 post-menopausal women who received 500 mg EPO compared to other 20 received 233 mg soybean oil extract, as a capsule twice a day for 8 weeks. The subjective and clinical assessments of Menopause Symptom Treatment Satisfaction, and Menopause-Specific Quality of Life. Data was collected by the researcher via face-to-face interviews with women at baseline and after 2 months of treatment. Results: In this study, Menopause Symptoms Treatment Satisfaction score was not significant within each group post treatment (P>0.05). While after 2 months of treatment, EPO significantly improved the quality of life by decreasing all MEN-QoL domains more than soybean oil, except for the sexual domain (P<0.01). Conclusions: This study revealed that both EPO and soya bean oil supplements had the beneficial effect in improving the postmenopausal quality of life with less treatment satisfaction.